Manufacture of n-Propyl Propionate Using Ion Exchange Resins: Reaction Kinetics and Feasibility of Reactive Distillation - Reshma R. Devale; Bipin S. Deogharkar; Yogesh S. Mahajan (Bulletin of Chemical Reaction Engineering & Catalysis, 2022)
Reaction kinetics of esterification of propionic acid with 1-propanol to produce n-propyl propionate using Amberlyst-15 as a catalyst was investigated in this work. Effect of various parameters was studied. Initially, the efficacy of different catalysts was investigated which revealed that Amberlyst-15 can be suitably used for the reaction. This was followed by mass transfer exclusion which included effect of agitation speed, catalyst size and calculation of Weisz-Prater Criterion. Parameters selected for kinetic study were mole ratio of propionic acid to 1-propanol, temperature, catalyst loading and initial water concentration. Catalyst reusability was also verified. Aspen      Custom Modeler (ACM) was used to regress kinetic parameters and a good match was obtained. Reactive Distillation (RD) runs in the batch mode were performed which showed that RD is a better option for process intensification (PI) for this reaction. Copyright © 2022 by Authors, Published by BCREC Group. This is an open access article under the CC BY-SA License (https://creativecommons.org/licenses/by-sa/4.0).